2018
DOI: 10.1159/000486772
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted Dental Pulp Stem Cells Migrate to Injured Area and Express Neural Markers in a Rat Model of Cerebral Ischemia

Abstract: Background/Aims: Ischemic stroke is a major cause of disability and mortality worldwide, while effective restorative treatments are limited at present. Stem cell transplantation holds therapeutic potential for ischemic vascular diseases and may provide an opportunity for neural regeneration. Dental pulp stem cells (DPSCs) origin from neural crest and have neuro-ectodermal features including proliferation and multilineage differentiation potentials. Methods: The rat model of middle cerebral artery occlusion (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 22 publications
0
25
0
Order By: Relevance
“…The comparative study of neuron death ratio in rats transplanted with SHED and cbMNC confirmed no From this study and previous studies, neuronal death reduction after stem cell transplantation prove the paracrine effects of transplanted stem cells. The paracrine effects thought can modulate neurogenesis, angiogenesis, and neuroplasticity at the brain after ischemic stroke (Zhang et al, 2018;Mita et al, 2015). The angiogenesis after cerebral ischemia (Zhang et al, 2018;Mita et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparative study of neuron death ratio in rats transplanted with SHED and cbMNC confirmed no From this study and previous studies, neuronal death reduction after stem cell transplantation prove the paracrine effects of transplanted stem cells. The paracrine effects thought can modulate neurogenesis, angiogenesis, and neuroplasticity at the brain after ischemic stroke (Zhang et al, 2018;Mita et al, 2015). The angiogenesis after cerebral ischemia (Zhang et al, 2018;Mita et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The paracrine effects thought can modulate neurogenesis, angiogenesis, and neuroplasticity at the brain after ischemic stroke (Zhang et al, 2018;Mita et al, 2015). The angiogenesis after cerebral ischemia (Zhang et al, 2018;Mita et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…However, among all the dental stem cells, SCAPs have shown the greatest potential for neurotrophic effects, indicating that SCAPs could be an optimal cell source for peripheral nerve repair. 47 Based on these above evidences, we hypothesize that DSCs could be ideal stem cell sources for central nerve repair. 41 It has been reported that DPSCs exosomes possess the ability to penetrate the blood-brain barrier and reduce or replace neuronal loss in Parkinson's disease.…”
Section: Usag E Of Dental S Tem Cell S In Nervous Sys Tem Impairmentmentioning
confidence: 93%
“…46 Moreover, it has been reported that intravenously administered DPSCs could migrate into ischaemic areas, attenuate stroke-induced inflammation and reduce infarct volumes and cerebral oedema. 47 Based on these above evidences, we hypothesize that DSCs could be ideal stem cell sources for central nerve repair. In conclusion, dental stem cells could be used in both peripheral and central nervous system disease treatments.…”
Section: Usag E Of Dental S Tem Cell S In Nervous Sys Tem Impairmentmentioning
confidence: 93%
“…A previous study has shown that human DPSCs could potentially differentiate into functional neural progenitor cells or neurons, which can integrate with other brain tissues [76]. Other studies showed that transplanted DPSCs were able to migrate to the boundaries of ischemic areas, differentiate into neuron-and astrocyte-like cells in the rat brain [61], and express neuronal and NSC markers such as βIII tubulin, doublecortin, nestin, and neurofilament [64]. However, very few DPSCs were able to survive in the ischemic brain, and most migrated to the peri-infarct areas where they differentiated mostly into astrocytes rather than neurons.…”
Section: Protective Effects Of Dental Pulp Stem Cells After Ischemic mentioning
confidence: 99%